2022
DOI: 10.3389/fpls.2022.948106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single major QTL and candidate gene(s) governing hull-less seed trait in pumpkin

Abstract: The hull-less pumpkin (Cucurbita pepo) seed does not require de-hulling before use for human consumption, as a result highly preferred by the oil, nut, and baking industries. In hull-less seeds, a single recessive gene is responsible for the absence of outer thick seed coat layers; however, the genomic region and gene(s) controlling the trait are unclear to date. In this study, four crosses attempted to derive F2 and backcross populations confirmed the single recessive gene inheritance of hull-less seed trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Therefore, we selected CMTp182 for the confirmation of hybridity of putative interspecific F 1 plants. In support to this, our recently published manuscript 22 identified a candidate genomic region linked to hull-less seed trait ranging from 1.80 to 3.86 Mb on chromosome 12 of C. pepo genome and also reported a linked KASP marker. Similar results are also reported by two other recently published studies in C. pepo 23 , 24 .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Therefore, we selected CMTp182 for the confirmation of hybridity of putative interspecific F 1 plants. In support to this, our recently published manuscript 22 identified a candidate genomic region linked to hull-less seed trait ranging from 1.80 to 3.86 Mb on chromosome 12 of C. pepo genome and also reported a linked KASP marker. Similar results are also reported by two other recently published studies in C. pepo 23 , 24 .…”
Section: Discussionmentioning
confidence: 60%
“…These results are similar to the previous reports in C. pepo by Stuart 40 , Zraidi et al 41 and Lelley et al 3 . More recently, along with monogenic recessive inheritance, hull-less seed trait has been mapped to chromosome 12 of C. pepo genome with 'NST1' (Cp4.1Lg12g04350) as the putative candidate gene [22][23][24] . However, segregation distortion observed in Family IV, might be due to incomplete representation of whole F 2 population in chi square analysis.…”
Section: Total Number Of F 2 Seeds Sownmentioning
confidence: 99%
See 1 more Smart Citation
“…Hull-less or naked seed mutants have been identified in all three Cucurbita species, which were all controlled by a single recessive gene (n or h) [2,[12][13][14]. The n locus in C. pepo has been fine-mapped, and the results from three independent studies all support the NAC transcription gene Cp4.1LG12g04350 (CpNST1) on Chromosome 12 of C. pepo as the most possible candidate gene [19,20,43]. CmoCh17G004790 (CmNST1) and Cp4.1LG12g04350 (CpNST1) are homologs in the C. pepo and C. moschata genomes (Supplemental File S2).…”
Section: Cmnst1 Is a Candidate Gene For The Naked Seed (N) Locusmentioning
confidence: 99%
“…durum-Aegilops longissima with high iron and zinc contents (Tiwari et al, 2008) and T. turgidum-Aegilops umbellulata with strong tillering ability, stripe rust resistance, and seed size-related traits (Song et al, 2019) have also been reported. Similarly in vegetables, the hull-less seed trait was transferred from Cucurbita pepo to Cucurbita moschata through interspecific hybridization (Kaur et al, 2023).…”
Section: Selfed Amphidiploid Derivativesmentioning
confidence: 99%